No-Fault Automobile Insurance in Manitoba : An Overview - Schnoor, Jeffrey (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1998)
In 1993, Manitoba followed Quebec's lead and became the second jurisdiction in North America to abolish the traditional tort system and adopt a pure no-fault compensation plan for victims of automobile accidents; the plan has been in operation since 1994. This paper begins with an examination of some of the events which led to this reform. It then reviews the scope of the plan (including consideration of a judgment of the Manitoba Court of Appeal on the subject) and gives an overview of the plan's operation, including the compensation provided by it and the provisions for review and appeal of decisions. At the end of the paper, an addendum summarizes (and briefly comments on) a review of the no-fault plan which was released following the completion of the paper.